Da'wa in Shihab & Shihab Youtube Content: Semiotic Analysis of “Islam Wasathiyyah, Islam yang di Tengah” Episode - Ikrimah, Fauziyah; Rindianto, M. Alief; Emeraldien, Fikry Zahria; Pratama, Muhammad Wahyu (Proceedings of International Conference on Da'wa and Communication, 2021)
The development of information and communication technology plays an important role in meeting the needs of people from various sectors of life, one of which is da'wah. Da'wa activities which are usually carried out face to face, can now be done anywhere and anytime without being constrained by time and place. Youtube is one of the platforms that is often used as a medium of da'wa because Youtube makes it easy to access and spread da'wa messages, especially when conflicts arise in the name of certain groups. This is because the resulting conflict is contrary to the principles of human life, harmony and peace. Therefore, to minimize the occurrence of these conflicts, the application of religious moderation is quite important and is expected to be a 'reducer' for the religious ways of extremist communities. To deal with this, we need some kind of da'wa content that invites people to tolerate and understand the differences, one of which is Shihab & Shihab's Youtube content "Wasathiyyah Islam, Islam in the middle."